Aerator System of Ventury Nozzle in Hydroponic for Cultivating Lettuce Plants - Sitti Nur Faridah; Abdul Azis; Tisha Aditya A. Jamaluddin; Alifah Agil Anugrah; Husnul Mubarak (Salaga Journal, 2024)
Many lettuce plants are grown hydroponically because they produce better quality.The problem with hydroponic systems is that the plant roots are submerged in the nutrient solution, therefore it will rot easily due to lack of oxygen in the root area. To overcome this problem, hydroponics with microbubble technology is applied. This research aims to determine the performance of the ventury dual nozzle in producing microbubbles and its effect on the growth and productivity of lettuce plants. This research was carried out by assembling a hydroponic system equipped with a ventury model aerator, measuring bubble characteristics using the image processing method and analyzing plant parameters using variance analysis. Ventury nozzle with a pressure of 260 KPa produces microbubbles measuring between 200 - 300 m and a spray range of 6.13 cm with a resistance of around 3.2-4.6 seconds. The use of a ventury nozzle model aerator increases dissolved oxygen and distributes it evenly in the hydroponic nutrient solution, thereby increasing the growth and yield of lettuce plants.